2021
DOI: 10.1136/bmjgh-2021-007145
|View full text |Cite
|
Sign up to set email alerts
|

Geographic barriers to establishing a successful hospital referral system in rural Madagascar

Abstract: BackgroundThe provision of emergency and hospital care has become an integral part of the global vision for universal health coverage. To strengthen secondary care systems, we need to accurately understand the time necessary for populations to reach a hospital. The goal of this study was to develop methods that accurately estimate referral and prehospital time for rural districts in low and middle-income countries. We used these estimates to assess how local geography can limit the impact of a strengthened ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Indeed, the relative paucity of rural patients in the HCA database result aligns with existing literature on rural access barriers to specialty care in low- and middle- income countries. For instance, a 2021 study in rural Madagascar found that even in the presence of referral programs strengthened by the health system, geographic barriers leading to increased referral travel times were a primary driver of diminished access to specialty care in rural Madagascar [ 24 ]. Of note, a large portion of HCA patients present for cardiac complications of RHD, which begins with an infectious etiology and is less likely to be adequately treated and prevented in rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the relative paucity of rural patients in the HCA database result aligns with existing literature on rural access barriers to specialty care in low- and middle- income countries. For instance, a 2021 study in rural Madagascar found that even in the presence of referral programs strengthened by the health system, geographic barriers leading to increased referral travel times were a primary driver of diminished access to specialty care in rural Madagascar [ 24 ]. Of note, a large portion of HCA patients present for cardiac complications of RHD, which begins with an infectious etiology and is less likely to be adequately treated and prevented in rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…We found that geographic barriers to healthcare access persist in Ifanadiana, even at the level of community healthcare. Other studies in Ifanadiana have found that, despite the installation of an intervention that has virtually removed user fees and improved the quality of care at all levels of the health system, geographic barriers persist and negatively impact hospital referrals (40), use of primary health centers (9), child vaccination coverage (41), and malaria case ascertainment (42). In addition, results from the IHOPE cohort in Ifanadiana showed that, while financial inequalities in the intervention catchment had been significantly reduced between This trend is not unique to Madagascar, and negative impacts of geographic accessibility on primary and secondary healthcare access are well studied (see Guagliardo (44) for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Children with geographical barriers in health care access, who lived further than 5 km from health facilities (around one third of the study population) were significantly more exposed to P. falciparum , which could have important implications for malaria elimination efforts in these areas. These results suggest that suboptimal testing and treatment of malaria infections in these areas, due to geographic barriers to access health care [ 52 ], could result in undetected pockets of malaria transmission that undermine elimination goals. Indeed, previous studies have shown that persistent geographic inequalities in health care access still exist in rural areas of Madagascar, with an exponential decrease in the use of health facilities over the first 5 km [ 53 ].…”
Section: Discussionmentioning
confidence: 99%